A unified viscoplastic model and strain rate–temperature equivalence of frozen soil under impact loading. (July 2021) - Zhang, Fulai; Zhu, Zhiwu; Ma, Wei; Zhou, Zhiwei; Fu, Tiantian
Highlights: A new and economical pulse shaping technology is proposed. The strain rate-temperature equivalence of frozen soil is analyzed and proposed. The adiabatic condition of frozen soil under a high strain rate is considered. The damage variable is associated with adiabatic heating. The model calculated results agree well with the experimental results. Abstract: Based on the double-pulse shaping technology, a method for obtaining long rising edge loading pulse by using the structural response of a pulse shaper is proposed. The traditional split Hopkinson pressure bar (SHPB) was improved to be suitable for testing the dynamic mechanical properties of low wave impedance materials. The dynamic mechanical properties of frozen soil at different temperatures and strain rates were tested using the improved SHPB equipment. The increase in the strength of frozen soil was associated with a decrease in temperature and increase in strain rate. The strain rate–temperature equivalence of frozen soil is proposed by regression analysis of the experimental data. The relationship between the temperature and strain rate of frozen soil satisfied the Arrhenius equation and could be explained by the thermal activation mechanism. The thermal softening characteristics of frozen soil caused by the adiabatic heating under impact loading were analyzed, and described by the damage variable driven by the adiabatic heating. The damage dynamic constitutive model is proposed based on the unified viscoplastic theory. The comparison between the model and experimental results indicate the applicability of the model.